2017
DOI: 10.1002/cctc.201700829
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Process Intensification by 3 D Printing of Catalytic Structures

Abstract: Small‐scale, intensified chemical reactors (i.e., process intensification) mediated by structured catalysts substantially diminishes the advantages of large‐scale gas‐to‐liquid (transport fuels) process plants and can be realized at low capital costs, minimum energy consumption, and zero/small CO2 footprints. Current structured‐catalysts approaches are complex and expensive; therefore, simple methods are crucial that are capable of depositing a desired geometry of catalysts into engineered channels. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Carbon monoliths were produced by 3D printing of carbon source materials (doped with additives) by extrusion followed by pyrolysis (carbonization) in an inert gas shield of nitrogen [ 73 , 74 ]. By Solid Free Forming with an ink loaded with metal precursors, poly(vinyl alcohol), and starch, the Ni and Mo-doped carbon structures were developed.…”
Section: 3d Printing Applications In Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon monoliths were produced by 3D printing of carbon source materials (doped with additives) by extrusion followed by pyrolysis (carbonization) in an inert gas shield of nitrogen [ 73 , 74 ]. By Solid Free Forming with an ink loaded with metal precursors, poly(vinyl alcohol), and starch, the Ni and Mo-doped carbon structures were developed.…”
Section: 3d Printing Applications In Heterogeneous Catalysismentioning
confidence: 99%
“…A reaction of syngas conversion to higher alcohols was performed. At high flow rates of the syngas feed (6000 h −1 ), the CO conversion dropped quickly to 16% with pelleted catalysts, while the structured catalysts converted 35% of the CO [ 73 ].…”
Section: 3d Printing Applications In Heterogeneous Catalysismentioning
confidence: 99%
“…Accordingly, ~ 90% of the exhaust emissions is converted after passing through the first ~ 10% of the monolith length because of the high flow rates of reactants and slow diffusion of remaining low concentration Fig. 11 a Conventional ceramic monoliths for catalytic converters [72], b DIW-printed alumina supports with Cu-based catalysts [74], c 3D NiMo/PVA catalytic structures for process intensification [75], d DLP-printed catalytic ceramic substrates [76], e small-scale test setup of 3D-printed lightweight ceramic microlattice for low-heat capacity reactors [Kim et al, unpublished], f 3D-printed Pd/C monolithic catalyst [77], g DLP-printed microarchitected graphene aerogels [78], h DIW-printed graphene aerogel microlattices [79] of pollutants. In addressing this issue, the monolith length is usually increased, thereby resulting in it occupying more space and requiring more of the expensive catalytic materials.…”
Section: Microarchitected Reactors For Energy Applicationsmentioning
confidence: 99%
“…A 3D carbon scaffold with catalyst-loaded carbon containing up to 25 wt% was tested in CO conversion at high feed flow rates (Fig. 11c) [75]. Ortona et al investigated the effect of exhibited topology on the mechanical and flow properties of new and novel architected catalytic substrates (Fig.…”
Section: Microarchitected Reactors For Energy Applicationsmentioning
confidence: 99%
“…In (bio-)chemical engineering, 3D printing methods can enable the fabrication of highly sophisticated, geometrically optimized reactors not producible by conventional methods (Parra-Cabrera et al, 2018 ), as has been shown for bed geometries of chromatography columns (Fee et al, 2014 ), heat exchangers (Fee, 2017 ) or microfluidic reactors (Konarova et al, 2017 ). 3D printing can also dramatically speed up the production of prototypes (Ngo et al, 2018 ), allowing the iterative testing of different designs.…”
Section: Introductionmentioning
confidence: 99%